PENGARUH KEJELASAN SASARAN ANGGARAN,KOMPETENSI APARATUR DESA,DAN SISTEM PENGENDALIAN INTERN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - I Wayan Pebriyanto; Ni Komang Sumadi (Hita Akuntansi dan Keuangan, 2021)
This research aims to examine and analyze the effect of clarity, budget targets, the competence village officials and the internal control system on the accountability of village fund management. The entire village apparatus in the Sukawati District Government, Gianyar Regency, totaling 12 villages in the Sukawati District, were used as the population in this study and the sample in this study were 95 people. The questionnaire was used as a tool to collect data and purposive sampling was used to determine the sample. Multiple linear regression analysis was used as an analytical technique. The clarity of budget objectives will not affect the accountability of the village and village government is the result of this research. Partially, only the ability of village officials has an influence on the accountability of village fund management at the Sukawati District Government Office, Gianyar Regency, while the clarity of budget targets and the internal control system has no effect on the accountability of village fund management at the Sukawati District Government Office, Gianyar Regency.